Effect of Botanical Pesticides on Soil Fertility of Coffee-Orchards - Panthi, Bhanu B.; Devkota, Bhupendra; Devkota, Jyoti U. (Journal of Agriculture and Environment, 2009)
Coffee (Coffea arabica; Rubiaceae) is a potential and emerging commercial crop. Coffee is planted in the midhills of Nepal (800 to 1250 meter above mean sea level) in Gulmi and Lalitpur districts. To control the major insect pests of coffee plant, locally prepared ‘jaibik bishadi’ (botanical pesticides) are used as alternatives of the synthetic insecticides. This study was undertaken to see the contribution of ‘jaibik bishadi’ in the fertility of the coffee orchards soil, for which soil samples from botanicals used and not used coffee orchards were collected to see the level of soil characteristics and soil nutrients such as soil texture, organic matter, soil nutrients (phosphorous and potassium). There was some difference in the soil texture of topsoil, but no difference could be seen in sand, silt and clay content of the subsoils from botanical used and not used orchards. The pH was significantly different between botanical used and not used soils, but such difference could not be observed between the topsoil and subsoil from the same sites. Jaibik bishadi used to control the coffee pests significantly contributed in the soil fertility, which could be seen in high positive correlation (r=0.9886) between organic matter and nitrogen in the soil. Keywords: Coffee, jaibik bishadi, topsoil, subsoil, soil fertility The Journal of Agriculture and Environment Vol:9, Jun.2008 page: 16-22